(Re)Considering normal: queering social norms for parents and teachers. - Bower, Laura A; Klecka, Cari L (Teaching Education, 2009)
Recent debates regarding same-sex marriage and gay and lesbian adoption highlight the role of schools as sociopolitical institutions. Accordingly, teachers operating within social norms have considerable influence through their interactions with students and their families. Previous research points to lesbian, gay, bisexual, and transgender (LGBT) parents' frustrations with their children's schools, particularly as teachers resist representing LGBT families within curricula and fail to intervene when homophobic comments are made. Yet teachers' capacity to embrace diverse family structures while adhering to cultural expectations for teachers remains unexplored. This study, rooted in queer theory, explores the social norms teachers name for parenting in school settings and the way teachers position LGBT parents within these norms. Findings point to social norms for teachers and parents which indicate that teachers operate within heteronormative frameworks. They consider heterosexuality to be normal, while positioning LGBT identities as deviant. This is troubling given documented connections between teacher attitudes and parental involvement and between parental involvement and student achievement. Unchecked, heteronormative practices may result in inequitable school experiences for LGBT parents and their children. Teacher education must minimize heteronormativity through equipping teachers to attend to their own notions and assumptions regarding the intersection of parenting and sexual orientation. © 2009 Taylor & Francis.
Keywords: Teacher socialization; Teacher thinking and knowledge; dept.cur